2014
DOI: 10.1186/1472-6920-14-101
|View full text |Cite
|
Sign up to set email alerts
|

Measuring changes in perception using the Student Perceptions of Physician-Pharmacist Interprofessional Clinical Education (SPICE) instrument

Abstract: BackgroundThe Student Perceptions of Physician-Pharmacist Interprofessional Clinical Education (SPICE) instrument contains 10 items, 3 factors (interprofessional teamwork and team-based practice, roles/responsibilities for collaborative practice, and patient outcomes from collaborative practice), and utilizes a five-point response scale (1 = strongly disagree, 5 = strongly agree). Given the SPICE instrument’s demonstrated validity and reliability, the objective of this study was to evaluate whether it was capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 18 publications
2
47
0
2
Order By: Relevance
“…[7][8][9][10][11]17,20,23 Shrader and colleagues demonstrated that student perceptions, collected with an attitudinal survey instrument, were not a significant predictor of clinical outcome scores, whereas teamwork scores, rated by trained observers using a checklist, were a significant predictor of clinical outcome scores. 11 Our standardized objective behavior assessment followed a similar model and involved trained observers evaluating student team behaviors using a checklist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11]17,20,23 Shrader and colleagues demonstrated that student perceptions, collected with an attitudinal survey instrument, were not a significant predictor of clinical outcome scores, whereas teamwork scores, rated by trained observers using a checklist, were a significant predictor of clinical outcome scores. 11 Our standardized objective behavior assessment followed a similar model and involved trained observers evaluating student team behaviors using a checklist.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, student perceptions of IPE were predominantly positive, which is similar to previously published literature. 8,11,[17][18][19][20][21][22][23] Out of the 156 students who completed the standardized objective behavioral assessment, 45 students subsequently completed the voluntary student evaluation survey for a response rate of 29%. Overall, the responses were positive (Table 1).…”
mentioning
confidence: 99%
“…[15][16][17] Several publications examine the development of assessments with regard to the broad outcomes of IPE programs as students prepare to graduate and enter practice. 16,[18][19][20][21][22][23] Examples include the validation of the interprofessional collaborative competency attainment survey (ICCAS) and the exploration of a tool derived from the IPE Core Competencies. 18,19 The Student Perceptions of Physician-Pharmacist Interprofessional Clinical Education (SPICE) instrument was developed by physicians and pharmacists to assess students participating in an interprofessional clinic.…”
Section: Developing An Ipe Assessment Planmentioning
confidence: 99%
“…20, 21 The creators of this tool found that the assessment of roles and responsibilities had the lowest reliability for the SPICE instrument, indicating that it remains a challenging domain to assess. The CATS tool was developed to assess knowledge of the professional roles of others as a component of team communication, function, and leadership.…”
Section: Developing An Ipe Assessment Planmentioning
confidence: 99%
“…Законодательство в этой сфере крайне расплывчато, однако даже одно-кратное употребление спайсов может негативно сказаться на здоровье [28].…”
Section: связь мотивации пищевого поведения и изучаемых параметровunclassified